KEPUTUSAN PEMBELIAN POLIS ASURANSI SINARMAS MSIG LIFE - Muhammad Syahputra; Robi Wijaya (Pasca Sarjana Universitas Satya Negara Indonesia, 2022)
Appropriate and effective marketing is the spearhead of the company's success. One of the effective and efficient marketing strategies in marketing is by optimizing the marketing mix. This study uses the 4P marketing mix (Product, price, palace and persona selling). The purpose of this study was to determine and analyze the effect (product, price, palace and persona selling) together on the decision to purchase the Sinarmas Msig Life Insurance Policy at Chanel Bank BJB Cikarang Branch. The research method used is causal associative with quantitative techniques. The population is 1084 people and 262 people meet the criteria. Sampling used the Slovin technique so that 158 samples were obtained. The test used is the instrument feasibility test, classical assumption test and hypothesis testing. The results of the study show that the tolerance value for all independent variables is greater than 0.100 and the VIF value for all independent variables is less than 10 so it can be concluded that all independent variables have no symptoms of multicollinearity. Fcount (44.962) is greater than Ftable (2.43) and the R2 value is 0.725, which means that the independent variable is able to explain the dependent variable by 72.5% and the remaining 27.5%. Based on this value, it can be concluded that the independent variables (X) in explaining the dependent variable (Y) are very strong or the value is more than 70%. This means that the independent variables used in this study affect the dependent variable. So it can be concluded that H0 is rejected and the hypothesis Ha is accepted. Based on the results of the study, it can be proven that the independent variables of product, price, place and personal selling together or simultaneously affect the purchasing decision variables of Sinarmas MSIG Life insurance policies.